Internalization of Islamic Values in Shaping Student Discipline in Pesantren-Based Madrasahs - Munif, Muhammad; Rohmah, Kamilatur; Rozi, Fathor (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2026)
The development of student discipline in Islamic boarding schools requires character education strategies that not only enforce formal rules but also involve the structured and contextual internalization of Islamic values amid social challenges and changing times. This study aims to describe the process of internalizing Islamic values in shaping student discipline at MAN 1 Probolinggo, which is located in the Nurul Jadid Islamic Boarding School environment. This study uses a qualitative approach with a field study type, with data collection techniques through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model. The results of the study show that the internalization of Islamic values in shaping student discipline is carried out through three main strategies, namely the role model of educators as moral figures, the integration of discipline values in Islamic Religious Education, and daily habits based on pesantren culture. The third strategy works synergistically and sustainably to shape students' discipline as religious awareness, not merely obedience to rules. The pesantren environment acts as a key supporting factor that reinforces the consistency of students' disciplined behavior in their daily lives. This study has implications for character development in Islamic boarding school-based madrasahs, particularly in building holistic student discipline.